Хангай-Хэнтийн пермийн далайн сүбдүкцийн орой дээр үүссэн вулкан-плутон бүслүүр ба плюмын интрүзивын тухай - Ж.Бямба; Д.Оролмаа; Ш.Алтаншагай; Б.Манзшир (Geological Issues, 2023)
In this article we are expressed our views about Khangai-Khentii folded zone and their surrounding structures of igneous rock as arched like as ‘’horse-shoe" structure to south west direction, described by scholars’ were Orogenic structure of Epi-Hercynian /Zonenshain,1973/; late Paleozoic orogeny /Mossakovskii.1974/; late Paleozoic rifting /Byamba,2001/; Permian volcano-plutonic association /Gavrilova. Orolmaa.1991/; volcano-plutonic zone /Badarch,2002/; terrain of active continental margin /Tumurtogoo, 2003/; intraplate arc, active continental margin /Byamba,2012/; mantle plume of north east Asia /Kuzmin. Yarmolyuk.2012/ etc. Today, from view of the plate tectonics theory and gathered data of regional geology, petrography, geochemistry, and isotope research, shows all the surrounding volcanic structures of Khangai-Khentii folded zone, are approximate aged, but geodynamic environments are different as continental arc. continental rifting and continental active margins like as differentiated igneous path thru the crust. But intra-fold zone, plume related intrusion complexes /Kuzmin, Yarmolyuk.2012/ are composed and dominant by plagio-granite, gabbro-diorite and diorite (M-type, occasionally I-type) has lead some to believe that formed from primitive magma.